Analysis and characterization of an atropisomeric ionomer containing quaternary ammonium groups. (11th April 2018) - Chen, Jyh-Chien; Chen, Ping-Yen; Chen, Han-Yu; Chen, Kuei-Hsien
Abstract: Polyethersulfone ionomers containing quaternary ammoniums were prepared for the applications on alkaline anion exchange membrane (AAEM) fuel cells. The ionomers were synthesized from 2, 2′-dimethyl-4, 4′-biphenyldiol and bis(4-chlorophenyl) sulfone via nucleophilic substitution followed by bromination, quaternization and anion exchange reaction. The biphenyl structure in polymer main chain exhibited atropisomerism after bromination, leading to the anisochronous signals of geminal protons on bromomethyl groups in 1 H NMR spectra. Model compounds were synthesized to confirm the atropisomerism by EI mass and 1 H NMR spectra. The resonance peaks from five possible repeating units of brominated polyethersulfones in the 1 H NMR spectra were identified and discussed in detail. The rotational barriers of biphenyl structures containing brominated methyl groups at 2 and 2′ positions were calculated by density functional theory. The properties of these polyethersulfone anion exchange membranes (AEMs) were characterized. Their IECs ranged from 0.81 to 1.75 mequiv/g. The corresponding water uptakes and dimensional changes were in the ranges of 19–42% and 12–38%, respectively. The tensile strength of an AEM (1.75MQAPES-OH) with an IEC of 1.75 mequiv/g remained 17 MPa even though the water uptake was 42%. The hydroxide conductivity of 1.75MQAPES-OH could reach 51.4 mS/cm at 98%RH and 80 °C. After alkaline stability test for 168 h, the AEMs degraded slightly in terms of their IECs and hydroxide conductivity. Graphical abstract: Highlights: Polyethersulfone ionomers containing quaternary ammoniums were prepared from a new diol, 2, 2′-dimethyl-4, 4′-biphenyldiol, for the applications on alkaline anion exchange membrane (AAEM) fuel cells. The biphenyl structure in polymer main chain exhibited atropisomerism after bromination, leading to the anisochronous signals of geminal protons on bromomethyl groups adjacent to rotation-limited chiral axis. Model compounds were synthesized to confirm the atropisomerism by EI mass and 1 H NMR spectra. The hydroxide conductivity of AEMs could reach 51.4 mS/cm at 98 %RH and 80 °C.